The Effect of Product and Service Quality on Customer Satisfaction Loyalty Priority Savings Bank Sumut Syariah - Rafika Afifah Angkat; Nursantri Yanti (Penerbit Jurnal Indonesia, 2023)
Customers are expected to remain loyal to the service provider because of the quality of the products and services. However, it's not easy to make customers happy. The goal of this study was to find out how Bank Sumut Syariah's priority savings and product quality affect customer loyalty and satisfaction. A qualitative research method is utilized in this study. The subjects of the study were Bank Sumut Syariah customers who fell into the priority category and had met the requirements. The literature review method was used for this study's data collection. Descriptive qualitative data analysis was used for the data analysis. Customer satisfaction, loyalty, and priority savings at Bank Sumut Syariah are positively correlated with product and service quality, according to the findings of this research.